GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 838304 species occurrences available in GBIF matching the query: TaxonKey: Mammalia Linnaeus, 1758 Geometry: POLYGON((-120.234375 34.885930,-120.234375 -59.175928,-29.53125 -59.175928,-29.53125 34.885930,-120.234375 34.885930)) HasCoordinate: true HasGeospatialIssue: false BasisOfRecord: Specimen or Literature Occurrence. The dataset includes 838304 records from 110 constituent datasets: 322 records from NYSM Mammals. 46173 records from UMMZ Mammal Collection. 33 records from invertebratezoology. 58458 records from Field Museum of Natural History (Zoology) Mammal Collection. 2 records from Bernice P. Bishop Museum. 29878 records from Mammal specimens. 5616 records from SBMNH Vertebrate Zoology. 82 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 3 records from Distribution ashore and breeding places of southern elephant seals (OBIS South America, SOUTHERN OCEAN SUB-NODE). 1379 records from CHAS Mammalogy. 54 records from Speothos Venaticus por Guillermo Gil. 20 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 1954 records from Deforestación y fragmentación del hábitat: consecuencias ecológicas sobre la fauna de mamíferos de la selva tropical estacional. 988 records from Vertebrados terrestres del parque nacional Cañón del Sumidero, Chiapas, México. 18871 records from UF Florida Museum of Natural History Mammals. 34 records from Invertebrate Zoology Division, Yale Peabody Museum. 5 records from Collection Aves (bird skins) SMF. 1733 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 419 records from Mamíferos voladores y no voladores del suroccidente colombiano. 799 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 344 records from UAM Mammal Collection (Arctos). 31373 records from LSUMZ Mammals Collection. 1519 records from Museum of Comparative Zoology, Harvard University. 1905 records from CUMV Mammal Collection (Arctos). 10 records from Australian Museum provider for OZCAM. 8 records from Distribución geográfica de las aves y los mamíferos de las zonas montanas de los estados de San Luis Potosí e Hidalgo circundantes de la Sierra Gorda. 4435 records from FHSM Mammals Collection. 1 records from UCM Mammal Collection (Arctos). 130 records from UTEP Vertebrates. 7 records from Biological and palaeontological collection and observation data MNHNL. 1 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 4 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 1 records from Orchid Herbarium Collection. 63864 records from TTU Mammals Collection. 191 records from Diversidad biológica y conservación del ecosistema de los perros de la pradera (Cymomys ludovicianus) en México. 1407 records from Mammal tissues, Division of Genomic Resources, UNM, Albuquerque, NM.. 11354 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 96 records from Inventario de los murciélagos de los parques nacionales Sierra de San Pedro Mártir y Constitución de 1857, Baja California, México. 8245 records from UCLA Donald R. Dickey Bird and Mammal Collection. 91071 records from MSB Mammal Collection (Arctos). 68078 records from MVZ Mammal Collection (Arctos). 2050 records from Colección Teriológica y Ornitológica de la Universidad Tecnológica del Chocó. 34 records from Mammal collection, Natural History Museum, University of Oslo. 13 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 59720 records from Mammalogy Collection - Royal Ontario Museum. 1406 records from NCSM Mammals Collection. 1406 records from Colección de mamíferos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 6046 records from CAS Mammalogy (MAM). 784 records from Diversidad de los mamíferos de la Reserva de la biósfera Tehuacán-Cuicatlán, Puebla-Oaxaca, México. 17 records from Colección de Aves y Mamíferos del Valle de Cuatrociénegas, Coah., México (UANL). 8798 records from Mammals housed at MHNG, Geneva. 2 records from Naturhistorisches Museum Mainz, Zoological Collection. 945 records from Estacion Biologica Donana - CSIC, Mammal Collection. 6 records from Museum Victoria provider for OZCAM. 12 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 785 records from Colección de Mamíferos Marinos del Centro Nacional Patagónico. 2965 records from Plan de vertebrados de la Patagonia. 12228 records from Angelo State Natural History Collections (ASNHC) - Mammalogy Collection. 2 records from CCBER Mammalogy Collection. 853 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Mamíferos. 3 records from Colección Nacional de Ornitología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 4336 records from UWBM Mammalogy Collection. 17818 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 5 records from MSB Host Collection (Arctos). 3 records from Western Australian Museum provider for OZCAM. 5593 records from AMNH Mammal Collections. 1 records from Collection Anatomie Histologie - SMF. 1 records from Instituto de Botánica Darwinion. 133 records from Mammal specimens. 1062 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 5458 records from Instituto de ciencias naturales. 159 records from South Australian Museum Australia provider for OZCAM. 151 records from ISU Mammals. 88 records from WNMU Mammal Collection (Arctos). 71 records from Cowan Tetrapod Collection - Mammals. 453 records from RBINS collections. 23 records from Biodiversidad en las propuestas para declaratoria de Áreas Protegidas en los Municipios de Dagua, Restrepo, La Cumbre y Vijes y un Grupo de Reservas Naturales de la Sociedad Civil. 3923 records from Tissues Specimens. 4109 records from Colección de mamíferos de la Universidad del Valle. 72641 records from KUBI Mammalogy Collection. 16160 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 698 records from DMNS Mammal Collection (Arctos). 110 records from Queensland Museum provider for OZCAM. 6 records from CNCR/Colección Nacional de Crustaceos. 83 records from P. W. Lund collection in the National History Museum of Denmark, Copenhagen. 35 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 2 records from Lund Museum of Zoology (MZLU). 35223 records from NMNH occurrence DwC-A. 416 records from Ohio State University Tetrapod Division - Mammal Collection (OSUM). 1268 records from MLZ Mammal Collection (Arctos). 1 records from Natural History Museum (London) Collection Specimens. 2701 records from Mammal specimens. 3190 records from USAC Mammals Collection. 15 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 19414 records from Mammals Specimens. 446 records from Inventario de la mastofauna en las reservas de la biosfera Desierto del Vizcaíno y Valle de los Cirios. 3285 records from Avistajes de espcies de valor especial en áreas protegidas del noreste de Argentina. 737 records from Colección Mastozoológica de la Universidad Industrial de Santander. 346 records from Cetacean distribution in the South Atlantic and South Pacific Ocean (AR-OBIS) (OBIS South America, SOUTHERN OCEAN SUB-NODE). 10597 records from New Mexico Biodiversity Collections Consortium database. 517 records from UWYMV Mammal Collection (Arctos). 4626 records from Mamíferos de los Parques Nacionales Lagunas de Montebello y Palenque, Chiapas. 1683 records from PSM Vertebrates Collection. 923 records from TTRS Mammals. 7 records from COMARGIS: Information System on Continental Margin Ecosystems. 5 records from Inventario florístico y faunístico del Parque Nacional Barranca del Cupatitzio, Michoacán. 43041 records from LACM Vertebrate Collection. 16 records from MVZ Hildebrand Collection (Arctos). 2021 records from NMMNH Mammal. 2473 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México.
Keywords: GBIF; biodiversity; species occurrences